2019
DOI: 10.1021/acsami.8b19321
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interfacial Bulk Heterojunction Technique for Enhanced Response in ZnO Nanogenerator

Abstract: In this paper, a direct sustainable approach for the development of a n-ZnO:p-CuO heterojunction (ZCH) through a simple grinding is reported to be an effective technique to enhance the piezoelectric performance of ZCH/polydimethylsiloxane (PDMS) nanocomposite-based nanogenerators (ZP-PNGs). We have first optimized the best concentration for ZnO/PDMS nanocomposite for the realization of the piezoelectric nanogenerator. Later, with the same configuration, we implemented a novel, simple, facile, frugal, and inexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…This is due to the fact that greater force gives rise to higher strain components according to the IEEE Standard on Piezoelectricity (1987), and the component of electrical displacement of the included piezoelectric components is linked to the functional stress. 27 Thus, a greater strain value gives rise to greater electric displacement in the material, which further increases the polarization density of the material. This characteristic of the PENG reflects its significant role in the applications of self-powered accelerometer or force sensor.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the fact that greater force gives rise to higher strain components according to the IEEE Standard on Piezoelectricity (1987), and the component of electrical displacement of the included piezoelectric components is linked to the functional stress. 27 Thus, a greater strain value gives rise to greater electric displacement in the material, which further increases the polarization density of the material. This characteristic of the PENG reflects its significant role in the applications of self-powered accelerometer or force sensor.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…26 Recently, Pandey et al fabricated a PENG through bulk heterojunction establishment of CuO−ZnO (p−n) to boost the harvest of energy from ZnO-based PENG. 27 Yin et al showed an enhanced performance of the ZnO-based PENG device through the formation of a heterojunction with p-type NiO. 28 On the other hand, a p−n homojunction produces an enhanced output due to the better junction interface and the upgraded chemical and mechanical durabilities of semiconductor p−n homojunction compared to the semiconductor−polymer heterojunctions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ZnO exhibits low dielectric constant (εr) and moderate piezoelectric strain constant (E), it possesses higher piezoelectric voltage constant and can be readily fabricated into different nanostructures for flexible PENGs. [16][17][18] In recent years, to improve the output performance and develop diversified applications, researchers have also developed various structures of ZnO such as nanowires, nanorods, nanosheets, and nanobows to construct piezoelectric nanogenerators. [19][20][21] 2D single crystal materials as high-performance piezoelectric materials have also attracted great attentions.…”
Section: Inorganic Piezoelectric Materialsmentioning
confidence: 99%
“…Hence, powering these devices is sporadically disadvantageous specifically in the remote areas because of size limitations and the need of frequent recharge . Different approaches have been adopted to harvest electrical energy from various alternative sources like solar, thermal, and mechanical energies. Motion-based mechanical energy is highly abundant and easily accessible in the ambient environment, which provides an important alternative route in obtaining cost-effective, carbon-emission-free, and sustainable electrical power sources. In this context, triboelectric nanogenerators (TENGs) are promising to generate electrical energy from motion-based mechanical energy that could power small and portable electronic devices and can act as self-powered sensors. The working principle of TENGs relies on the charge affinity between two active materials surfaces, where at least one material is nonconducting in nature.…”
Section: Introductionmentioning
confidence: 99%